Benzyl N '-(1-methyl-1H-indol-3-ylmethylidene)hydrazinecarbodithioate - Khaledi, H.; Ng, S.W.; Ali, Hapipah Mohd (International Union of Crystallography, 2008)
The N'-(1-methyl-1H-indol-3-ylmethylidene)hydrazinecarbodithioate portion of the title molecule, C(18)H(17)N(3)S(2), is nearly planar; this unit and the phenyl ring subtend an angle of 112.9 (2)degrees at the methylene C atom.